2020
DOI: 10.21203/rs.3.rs-18691/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic polymorphism and natural selection of circumsporozoite protein in Myanmar Plasmodium vivax

Abstract: Background: Circumsporozoite surface protein (CSP) of malaria parasites has been recognized as one of the leading vaccine candidates. Clinical trials of vaccines for vivax malaria incorporating Plasmodium vivax CSP (PvCSP) have demonstrated their effectiveness in preventing malaria, at least in part. However, genetic diversity of PvCSP in the natural population is still a major concern.Methods: A total of 171 blood samples collected from patients infected with Plasmodium vivax in Myanmar analysed in this study… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
16
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 27 publications
5
16
1
Order By: Relevance
“…In the present study, the genetic polymorphism in the pvcsp and pvmsp-1 genes were studied in detail. The results of the study support the findings of the previously published data showing that VK210 strain is predominant type with the prevalence rate ranging between 56-100% in Iran [20,24], Myanmar [15,40], Brazil [39], India [14,49], Thailand [41,42], Azerbaijan [19], China [13,42] and Mexico [43]. There are only few malaria endemic areas where VK247 isolates are commonly present [39].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In the present study, the genetic polymorphism in the pvcsp and pvmsp-1 genes were studied in detail. The results of the study support the findings of the previously published data showing that VK210 strain is predominant type with the prevalence rate ranging between 56-100% in Iran [20,24], Myanmar [15,40], Brazil [39], India [14,49], Thailand [41,42], Azerbaijan [19], China [13,42] and Mexico [43]. There are only few malaria endemic areas where VK247 isolates are commonly present [39].…”
Section: Discussionsupporting
confidence: 89%
“…The analysis of CRR region of Pakistani pvcsp isolates is indicative of positive selection when compared with pvcsp isolates of Iran and India. The negative Tajima's D values of Myanmar pvcsp population imply purifying negative selection [15]. The evidence from the previous studies has reported that the arrangements and numbers of PRMs in CRR are indicative of occurrence of phenomenon of natural selection on the pvcsp isolates [15,45,46].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The analysis of CRR region of Pakistani PvCSP isolates is indicative of positive selection when compared with PvCSP isolates of Iran and India. The negative Tajima's D values of Myanmar PvCSP population imply purifying negative selection [15]. The evidence from the previous studies has reported that the arrangements and numbers of PRMs in CRR are indicative of occurrence of phenomenon of natural selection on the PvCSP isolates [45,46].…”
Section: Discussionmentioning
confidence: 92%
“…Genetic sequences of PvCSP and PvMSP-1 are being used to understand the genetic diversity [11][12][13]. PvCSP, a highly immunogenic sporozoite surface protein, hence a good vaccine candidate, is encoded by single copy gene [8] and comprises of a central repeat domain that varies across Plasmodium species having two non-repetitive domains at N-and C-terminals [14,15]. The varying degree of number of peptides in the central repeat region reveals three variants of P. vivax namely VK210, VK247, P. vivax-like [16,17].…”
Section: Introductionmentioning
confidence: 99%